Validation of Psoas Muscle Index as a predictor of successful extubation in elderly intensive care patients: a retrospective cohort study. Issue 1 (12th November 2020) - Kobori, Fumimasa; Azuma, Kazunari; Mishima, Shiro; Oda, Jun
Abstract : Aim: Extubation failure–associated factors have not been investigated in elderly patients. We hypothesized that psoas cross‐sectional area, an emerging indicator of frailty, can be a predictor of extubation outcomes. Methods: This retrospective study analyzed data from patients admitted between January and April 2016 at the mixed medical intensive care unit (ICU) of the Tokyo Medical University Hospital. Patients were considered eligible if aged 65 years or older, required intubation at the emergency room, and were admitted to ICU for over 24 h. Overall, 39 ICU patients were eligible and categorized into two groups: extubation success ( n  = 24) and extubation failure ( n  = 15) groups. The psoas cross‐sectional area was measured at the third lumbar level on computer tomography images. Psoas Muscle Index (PMI) was defined as the psoas cross‐sectional area/height 2 . Primary outcome was to evaluate differences between the psoas cross‐sectional area and f(PMI) between the groups, if any. Results: Both groups were comparable in terms of demographic characteristics. Psoas cross‐sectional area (extubation success group, 1, 776.5 ± 498.2 mm 2, extubation failure group, 1, 391.2 ± 589.4 mm 2 ; P  = 0.022) and PMI (extubation success group, 1, 089 ± 270.7 mm 2 /m 2, extubation failure group, 889 ± 338.5 mm 2 /m 2 ; P  = 0.032) were significantly greater in the extubation success group than in the extubation failure group. Conclusions: The psoas cross‐sectional area and PMI can predict extubation outcomes in elderly intensive care patients. Abstract : The psoas cross‐sectional area and Psoas Muscle Index can predict extubation outcomes in elderly intensive care patients.